SENSE CONSTITUENT AND COGNITION: ON THE WAY TOWARD MEANING - Sergey N. Bredikhin (Вестник Северо-Кавказского федерального университета, 2022)
The aim of this study is to analyze the categorization process of distinguish features in sense structure as the basis of meaning building. The analysis is based on the principles of prototype sense denotative criteria signi- fication, in organizing and encoding the basis categorization level as the core structure of dominant-noems.